A highly selective Schiff base fluorescent chemosensor for Lu3+. Issue 44 (1st November 2017) - Wang, Lina; Tang, Juanjuan; Sui, Ning; Yang, Xing; Zhang, Luyao; Yao, Xiaojun; Zhou, Qinfei; Xiao, Hailian; Kuang, Shaoping; Yu, William W.
Abstract : A Schiff base derivative shows high selectivity to Lu 3+ in both abiotic systems and living cells. Abstract : A Schiff base derivative, N -(3-methoxy-4-hydroxybenzylidene)salicyloylhydrazone (L ), shows high selectivity to Lu 3+ not only in abiotic systems but also in living cells with fluorescence. The presence of PVP can increase the fluorescence intensity. The fluorescence enhancement is presumably due to a combinational effect of intramolecular charge transfer (ICT) and excited-state intra/intermolecular proton transfer (ESPT) during the chelation ofL to Lu 3+ in a 2 : 1 complex mode.